Acute Bouts of Exercising Improved Mood, Rumination and Social Interaction in Inpatients With Mental Disorders - Brand, Serge; Colledge, Flora; Ludyga, Sebastian; Emmenegger, Raphael; Kalak, Nadeem; Sadeghi Bahmani, Dena; Holsboer-Trachsler, Edith; Pühse, Uwe; Gerber, Markus (Frontiers in Psychology, 2018)
Background: Studies at the macro level (such as longer-term interventions) showed that physical activity impacts positively on cognitive-emotional processes of patients with mental disorders. However, research focusing on the immediate impact of acute bouts of exercise (micro level) are missing. The aim of the present study was therefore to investigate whether and to what extent single bouts of moderately-intense exercise can influence dimensions of psychological functioning in inpatients with mental disorders. Method: 129 inpatients (mean age: 38.16 years; 50.4% females) took part and completed a questionnaire both immediately before and immediately after exercising. Thirty inpatients completed the questionnaires a second time in the same week. The questionnaire covered socio-demographic and illness-related information. Further, the questionnaire asked about current psychological states such as mood, rumination, social interactions, and attention and tiredness and physical strengths as a proxy of physiological states. Results: Psychological states improved from pre- to post-session. Improvements were observed for mood, social interactions, attention, and physical strengths. Likewise, rumination and tiredness decreased. Mood, rumination, and tiredness further improved, when patients completed the questionnaires the second time in the same week. Conclusions: At micro level, single bouts of exercise impacted positively on cognitive-emotional processes such as mood, rumination, attention and social interactions, and physiological states of tiredness and physical strengths among in-patients with mental disorders. In addition, further improvements were observed, if patients participated in physical activities a second time.